The Role of Micronutrients in Gastrointestinal Function and Protection in Stroke Patients: Literature Review - Ega Fadila; Aryanti R. Bamahry; Muhammad Fadli Said (Journal La Medihealtico, 2025)
Stroke is a serious health problem. Micronutrients are nutrients that the body needs in small amounts, such as vitamins and minerals. Neurological deficits due to acute stroke can cause malnutrition during hospital treatment. To determine the role of micronutrients in gastrointestinal function and protection in stroke patients. A systematic-narrative literature review following the PRISMA 2020 guidelines. Data sources included SINTA, Scopus, ClinicalKey, as well as proceedings and dissertations published between 2020 and 2025. Articles were assessed based on methodological quality and relevance to the management of stroke patients in Indonesia. A thematic analysis was conducted to synthesize the latest evidence. Several studies showed that micronutrients such as vitamins A, C, D, E, B9 (folate), B12, zinc, magnesium, and selenium play an important role in maintaining intestinal mucosal integrity, reducing oxidative stress and inflammation, and supporting intestinal microbiota balance in stroke patients. Adequate micronutrient intake helps prevent gastrointestinal complications and accelerates post-stroke motor and cognitive recovery. Micronutrient optimization is important for maintaining gastrointestinal function in stroke patients, supporting recovery, preventing complications, and improving quality of life.